Analisis Kesetaraan Gender Terhadap Pembangunan Perekonomian Daerah Wilayah Pro Gender di Kabupaten/Kota Sumatera Barat - Erra Farazila; Novya Zulva Riani; Maizul Rahmizal (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study was conducted to determine how gender equality in the fields ofeducation, health, and per capita expenditure on the economy of pro-genderregions in districts / cities in West Sumatra. This type of research isquantitative research, the data used is panel data, namely from 19 districts /cities in West Sumatra in 2017-2022, which is secondary data obtained fromthe Central Statistics Agency (BPS). The results showed that: 1) theclassification of gender equality in the field of education on the regionaleconomy there are 9 regions in developed areas that are pro-gender, 2 regionsin potential areas that are pro-gender, 4 in developing areas that are not progenderand 4 regions in underdeveloped areas that are not pro-gender. 2) Theclassification of gender equality in the health sector has the results that thereare 6 regions in developed areas that are pro-gender, 6 regions in potentialareas that are pro-gender, 7 regions in developing areas that are not progenderand there are no regions in underdeveloped areas that are not progender.3) The classification of gender equality in the field of per capitaexpenditure has the results of 7 regions in developed areas that are pro-gender,1 region in a potential area that is pro-gender, 6 regions in developing areasthat are not pro-gender and 4 regions in underdeveloped areas that are notpro-gender.